Economic analysis for sizing of sugarcane (Saccharum spp.) mechanized harvesting - Santos, Neisvaldo B. Dos; Silva, Rouverson P. [UNESP]; Gadanha Junior, Casimiro D. (Associação Brasileira de Engenharia Agrícola, 2014)
Sugarcane has a significant role on Brazilian agribusiness economy. The harvesting cane is considered as one of the most important operations of the process for it has to attend the raw material demanded by the sugar mill in quality and a competitive cost. The objective of this work it is it of analyzing, of systemic way, the variables influence on economical and operational performance in sugarcane mechanized harvesting process for sizing of machines. For this purpose a model called ColheCana, was developed in a spreadsheet and in a programming language. The results showed that the field efficiency and harvester´s initial value are variables of great impact in the cost and that there is a maximum area that one equipment can attend and for this area the cost is minimum.

A cultura da cana-de-açúcar tem significativa participação na economia do agronegócio brasileiro. A colheita de cana é considerada como uma das operações mais importantes, pois deve atender à demanda de matéria-prima requerida pela Usina com qualidade e custo competitivo. O objetivo deste trabalho foi analisar, de modo sistêmico, a influência das variáveis no desempenho operacional e econômico do processo de colheita mecanizada da cana-de-açúcar para o dimensionamento das máquinas. Para tanto, foi desenvolvido um modelo, denominado de ColheCana, em planilha eletrônica e em linguagem de programação. Os resultados evidenciaram que a eficiência de campo e o valor inicial das colhedoras são variáveis de grande impacto no custo e que existe uma área máxima a que um equipamento pode atender para a qual o custo é mínimo.
Análise econômica para o dimensionamento da colheita mecanizada de cana-de-açúcar (Saccharum spp.)
Keywords: mecanização agrícola; colhedora de cana; modelo computacional; agricultural mechanization; sugarcane harvester; computational model